CLINICAL CHARACTERISTICS OF NONSPECIFIC INTERSTITIAL PNEUMONIA (World Bulletin of Public Health, 2024)
To identify the frequency of occurrence, clinical characteristics, and diagnosis of interstitial pneumonia in the pulmonary department of hospitals, a retrospective analysis of case histories of 22 patients with nonspecific interstitial pneumonia who were hospitalized in the pulmonology department of the Samarkand medical association was performed. An increase was found in patients with interstitial lung diseases, which are observed more often in women of working age, with prevalence of dyspnea, weakness, cough in the clinic, and the importance of the use of imaging technologies is indicated. Consultation of a pulmonologist is recommended for patients with rheumatic diseases
Keywords: nonspecific interstitial pneumonia; clinical signs; diagnosis; rheumatic diseases